Physiological demands of water polo games with different levels of competitiveness - Platanou, T.; Nikolopoulos, G. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION Literature review shows limited information available regarding the actual energy demands of water polo games. Former studies have examined the energy demands of water polo, without taking into consideration the specific characteristics of each game as for example, the level of difficulty. PURPOSE The aim of this study was to present the intensity of the water polo games with vigorous competition (i.e. two goals difference) and without vigorous competition (i.e. more than two goals difference). In addition, to examine the hypothesis that players rely more on anaerobic metabolism in the former than in the latter condition. METHODS For the duration of sixteen games (eight with two goals difference and eight with more than two goals difference), heart rate was continuously monitored in 24 players. In addition capillary blood samples were collected at the end of each period, for lactate concentration determination. Before the games, the maximum heart rate (HRmax) was determined during a tethered swimming test. Finally HR at anaerobic threshold, as determined by blood lactate concentration, was recorded. RESULTS The average heart rate during the games with two goals difference was 158±18 beats/min, slightly higher than the HR at the anaerobic threshold (155±12 beats/min) and significantly greater (p< 0.001) than the average heart rate of the games with more than two goals difference (154±17 beats/min). Likewise, blood lactate accumulation after the games with two goals difference was 4,4±2,2 mmol/l, again slightly higher than blood lactate at the anaerobic threshold (4,0±1 mmol/l) and significantly greater (p< 0,001) than the average lactate in the games with more than two goals difference (3,4±1,5 mmol/l). In addition, during the games with two goals difference players played most of time at high exercise intensity limits (85-100 % HR max), compared with the games with more than two goal difference. DISCUSSION It seems that the different level of the opponents significantly affects the energy demands of water polo. Actually, games energy demands depend on the goal difference between the teams. The anaerobic metabolism is mostly used during the games with two goal difference. However, during the games with more than two goals difference the percentage of contribution of anaerobic energy system is significantly lower and the aerobic metabolism takes place.